Primary school health content gaps and school curriculum implications - Prihantini Prihantini; Ai Rukmini; Willius Kogoya; Bernadetha Nadeak; Atep Jejen (Jurnal Konseling dan Pendidikan)
This study aims to identify specific discrepancies between the health education content taught in primary schools and the content that should ideally be taught. The content taught includes personal hygiene, nutrition and healthy eating, and the dangers of smoking and addictive substances. Health education at the primary school age is particularly important because children at this stage are vulnerable to health risks, and early education has been shown to be effective in shaping sustainable health-conscious attitudes. The study employed a survey method in the Greater Bandung area, encompassing Bandung City, Cimahi City, Bandung Regency, and West Bandung Regency.A sample of 20 schools and 120 students was selected proportionately at random.Data were collected through structured questionnaires and in-depth interviews, and were analyzed descriptively to identify gaps in health education content. The results indicated that 65% of students did not receive adequate education on personal hygiene, including proper handwashing, bathing, and hair washing. Furthermore, 58% of students lacked sufficient understanding about nutrition and healthy eating, while 72% did not receive education about the dangers of smoking and addictive substances.These findings underscore the necessity to fortify the health education curriculum in primary schools. This study proposes the formulation of a more comprehensive and integrated school-based curriculum, including the delineation of specific time allocations for health education and the training of teachers in the effective delivery of health materials.Practical implications of this study include the necessity of raising awareness of the paramount importance of health education through collaboration between schools, parents, and communities to foster an environment that supports children's health.